Allumiere, Italien: Früher Bergbau in Mittelitalien - Steiniger, Daniel (e-Forschungsberichte des DAI, 2023)
Central Italy has been famous for its metal finds since the Chalcolithic. Large copper deposits suggest local exploitation, but little is known about prehistoric copper mining and production. A recent research project between 2010– 2013 was able to present new evidence in the form of stone-hammers from the Monti della Tolfa (Latium). Although it is not possible to date the exploitation of the copper mine precisely at the moment, stratigraphic evidence suggests that it predates the Late Bronze Age.